Decoding the brain’s ATG8 paralog code: LC3–GABARAP specialization at synapses and the astrocyte–neuron interface - Choi, Haneul; Lee, Seung-Min; Lee, Jin-A. (Frontiers in Cell and Developmental Biology, 2026)
Macroautophagy is essential for the long-term health of neurons and astrocytes in the central nervous system (CNS). The six mammalian ATG8 paralogs (LC3A/B/C and GABARAP/GABARAPL1/L2) exhibit an emerging “ATG8 code”—a division of labor among these proteins that assigns specialized roles in the autophagy pathway to each paralog, enabling fine-tuned proteostasis at synapses and the astrocyte–neuron interface. This review synthesizes how LC3 versus GABARAP mediate distinct steps of autophagy (LC3 primarily governs cargo recruitment and phagophore expansion, whereas GABARAP drives autophagosome maturation, transport, and lysosomal fusion) and how these molecular distinctions translate into functional differences in neurons versus astrocytes. Neurons coordinate autophagy across long axons and synapses: presynaptic autophagy clears aging synaptic vesicles and organelles, while postsynaptic autophagy modulates receptor turnover and synaptic plasticity. Astrocytes, by contrast, leverage autophagy for metabolic support and clearance of extracellular debris (e.g., amyloid-β plaques), interfacing with neuronal autophagy via transcellular mechanisms. Dysregulation of these processes underlies diverse CNS disorders: impaired autophagic flux and aggregate clearance contribute to neurodegenerative diseases (Alzheimer’s and Parkinson’s), whereas selective autophagy deficits at synapses disrupt circuit homeostasis (implicated in epilepsy and autism). Finally, we highlight emerging methodologies—from multi-omics and live imaging to optogenetics and targeted therapeutics—that are illuminating this specialized autophagy network and opening novel avenues for intervention.